POTENSI CADANGAN KARBON PADA BIOMASSA DI HUTAN LINDUNG LIANG ANGGANG KOTA BANJARBARU - Ubai Dillah; Mufidah Asy'ari; Suyanto Suyanto (Jurnal Sylva Scienteae, 2024)
The potential forests decreasing become global warming, thus affecting the occurrence of global climate change. Climate change in turn has impacted on the survival living. This is marked by appearance of extreme weather. The other phenomena in the form of natural disasters, namely: drought, floods, rain, storms, high waves, tidal floods, and so on. The goal of this case was to specify the potential for carbon stocks of biomass in Liang Anggang protected forest, Banjarbaru City. The chosen research method is using primary and secondary data. Secondary data was obtained from research, while primary data was obtained from field observations by taking several plots of biomass measurements. Plot placement is determined based on the normalized different vegetation index (NDVI). Primary data used a purposive sampling method from 12 plots from three NDVI classes, namely dark green (dense), light green (medium), and yellow (rare). The shape of the plot is in the form of a square measuring 30x30 m for the tree level, which contains plots of 10x10 for the pole level, 5x5 m for the sapling level, and 0.5x0.5 m for observations of understorey biomass and seedling level. The amount of potential biomass is counted using the appropriate allometric equation. The results of this study indicate overall potential for carbon stocks in an area of 960 ha is 37,739.60 tonnes with an average carbon reserve of 39.31 tonnes/ha, including a very low potential when compared to the potential for carbon stocks in general peatlandsPotensi hutan semakin berkurang mengakibatkan pemanasan global, sehingga mempengaruhi terjadinya perubahan iklim global. Perubahan iklim global tersebut pada gilirannya berdampak pada kelangsungan makhluk hidup. Hal ini di tandai dengan munculnya cuaca ekstrim. Selain itu, munculnya fenomena lain berupa bencana alam, yaitu: kekeringan, banjir, hujan, badai, gelombang tinggi, banjir rob, dan sebagainya. Tujuan penelitian ini untuk mengetahui besaran potensi cadangan karbon pada biomassa di hutan lindung Liang Anggang Kota Banjarbaru. Metode penelitian yang dipilih adalah menggunakan data primer dan sekunder, dimana data sekunder didapat pada studi Pustaka sebelumnya, sedangkan data primer didapat dari observasi ke lapangan dengan mengambil beberapa plot pengukuran biomassa. Peletakan plot ditentukan berdasarkan indeks nilai kehijauan (Normalized Different Vegetation Index / NDVI). Data primer di lapangan diambil menggunakan metode purposive sampling 12 plot dari tiga klas indeks kehijauan NDVI yaitu hijau tua (rapat), hijau muda (sedang), dan kuning (jarang). Bentuk plot berupa bujur sangkar berukuran 30x30 m pada tingkat pohon, didalamnya berisi plot 10x10 m sebagai plot tingkat tiang, 5x5 m tingkat pancang, dan 0,5x0,5 m pengamatan biomassa tumbuhan bawah dan tingkat semai. Besaran potensi biomassa dihitung menggunakan persamaan allometric yang sesuai. Hasil penelitian ini menunjukkan potensi cadangan karbon secara keseluruhan dalam luasan 960 ha adalah sebesar 37.739,60 ton dengan rataan cadangan karbonnya adalah 39,31 ton/ha, termasuk potensi sangat kurang bila dibandingkan dengan potensi cadangan karbon yang umum di lahan gambut